The Relationship Between Clinical Communication Skills of Pediatric Nurses and Children’s Trust in Nurses: The Mediating Role of Emotional Intelligence - Chong Q; Zhan Z; Peng M; Li X (Nursing: Research and Reviews, 2025)
Qingqing Chong,1,* Zhiheng Zhan,2,* Mingqi Peng,3,* Xianwen Li4 1Department of Orthopaedics Surgery, Children’s Hospital of Nanjing Medical University, Nanjing, Jiangsu Province, 210000, People’s Republic of China; 2Department of Respiratory, Children’s Hospital of Nanjing Medical University, Nanjing, 210008, People’s Republic of China; 3Department of Nursing, Children’s Hospital of Nanjing Medical University, Nanjing, 210008, People’s Republic of China; 4School of Nursing, Nanjing Medical University, Nanjing, 211103, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xianwen Li, Email xwli0201@njmu.edu.cnAim: To explore the mediating role of emotional intelligence in the relationship between pediatric nurses’ clinical communication skills and children’s trust in nurses.Methods: A correlational, cross-sectional non-experimental study was conducted in the pediatric department of a tertiary hospital in Nanjing, China. Using a purposive sampling method, 385 hospitalized children were recruited to complete the Children’s Trust in Nurses Scale. 385 nurses caring for these children were selected based on a 1:1 matching principle to complete general information questionnaires, clinical communication skills scales, and emotional intelligence scales.Results: The results of this study showed that nurses’ total communication skills score was (239.27 ± 33.25), emotional intelligence score was (62.51 ± 9.03), and children’s trust in nurses score was (28.85 ± 6.48). The direct effect of clinical communication skills on children’s trust in nurses was significant with an effect value of 0.074; emotional intelligence as a mediating effect was 0.06, accounting for 44.8% of the total effect.Conclusion: Nursing administrators can enhance the trust between pediatric patients and nurses by training nurses to improve their emotional intelligence and clinical communication skills.Keywords: children’s trust in nurses, clinical communication skills, emotional intelligence, pediatric nurses